Jawabanmu

Jawaban paling cerdas!
2014-04-21T08:54:46+07:00
2(8a^2 + 12a) + 2(8a^2 - 8a) + 2(4a^2 - 4a + 6a - 6)
16a^2 + 24a +16a^2 - 16a + 8a^2 - 8a + 12a - 12
40a^2 +12a - 12
makasih ya
iya,tp cek kembali siapa tau ada salah hitung, dek ..
2014-04-21T09:05:57+07:00
=> 2 [ (2a+3) x (4a) ] = 4a + 6 x 8a = 32a² + 6
=> 2 [ (4a) x (2a-2) ] = 8a x 4a - 4 = 32a² - 4
=> 2 [ (2a+3) x (2a-2) ] = 4a + 6 x 4a - 4 = 16a² + 2

jadi, 32a² + 6 + 32a² - 4 + 16a² + 2 = 32a² + 32a² + 16a² + 6 - 4 + 2
                                                   = 80a² + 4

=> klw jawabannya salah mohon maaf ya